Optimizing Corporate Branding: The Role of Artificial Intelligence In Business Transformation of IQOS - Krisprimandoyo, Denpharanto Agung (PT. Riset Press International, 2024)
Corporate branding stands as a pivotal facet of a company's identity, wielding substantial influence over consumer perceptions and confidence. In the contemporary digital landscape, the optimization of corporate branding demands innovative methodologies. Artificial intelligence (AI) assumes a pivotal role in revolutionizing how companies conceptualize and manage their brand image. Leveraging AI-powered tools and algorithms furnishes invaluable insights into consumer behaviors, preferences, and prevailing market trends, empowering companies to make data-informed decisions, tailor branding strategies, and elevate overall customer experiences. Furthermore, AI's integration augments brand management endeavors by expediting the analysis of feedback, enabling swift adaptation to dynamic market shifts and evolving consumer sentiments. This research significantly contributes to both academic discourse and industry practices by elucidating AI's transformative prowess and furnishing guidance on embedding strategic branding approaches aligned with the exigencies of the digital era. Through an amalgamation of case studies and theoretical frameworks, this article illuminates the symbiotic relationship between AI and corporate branding, underscoring their mutually advantageous alliance within the sphere of business transformation.